Ambient vibration testing and seismic performance of precast I beam bridges on a high-speed railway line - Toydemir, Burak; Kocak, Ali; Sevim, Baris; Zengin, Basak (TECHNO-PRESS, 2017)
In this study, the seismic performance levels of four bridges are determined using finite element modeling based on ambient vibration testing. The study includes finite element modeling, analytical modal analyses, ambient vibration testing and earthquake analyses of the bridges. For the purpose, four prestressed precast I beam bridges that were constructed for the Ankara-Sivas high speed railway line are selected for analytical and experimental studies. In the study, firstly a literature review related to the dynamic behavior of bridges especially precast beam bridges is given and then the formulation part related to ambient vibration testing and structural performance according to Turkish Seismic Code ( 2007) is presented. Next, 3D finite element models of the bridge are described and modeled using LARSA 4D software, and analytical dynamic characteristics are obtained. Then ambient vibration testing conducted on the bridges under natural excitations and experimental natural frequencies are estimated. Lastly, time history analyses of the bridges under the 1999 Kocaeli, 1992 Erzincan, and 1999 Duzce Earthquakes are performed and seismic performance levels according to TSC2007 are determined. The results show that the damage on the bridges is all under the minimum damage limit which is in the minimum damage region under all three earthquakes.
Keywords: ambient vibration testing; dynamic characteristic; finite element modeling; precast I beam bridge; seismic performance level; CABLE-STAYED BRIDGES; GROUND MOTION; CONCRETE; PIERS; DESIGN; CONSTRUCTION; PREDICTION; DECKS; FRP; Construction & Building Technology; Engineering; Materials Science